Advokasi Kepatuhan Perizinan UMKM oleh Program Studi Hukum UMSIDA - Adelia Alvisa W; Noor Fatimah Mediawati (Journal Customary Law, 2025)
This study examines the issue of low legal compliance and business legality among Micro, Small, and Medium Enterprises (MSMEs) in Sidoarjo Regency, particularly regarding business licensing through the Online Single Submission (OSS) system and the issuance of Business Identification Numbers (NIB). The purpose of this research is to analyze the role of assistance provided by the Law Study Program of Universitas Muhammadiyah Sidoarjo in improving MSME legal compliance. This research employs an empirical juridical method with a qualitative descriptive approach using interviews, observations, and documentation. The results indicate that legal socialization, OSS training, and technical assistance in NIB issuance effectively increase legal awareness and understanding among MSMEs. In conclusion, legal assistance has a positive contribution to improving MSME compliance and creates a significant impact on sustainable and lawful business development.